929. A Nationwide Survey on the Role of Antimicrobial Stewardship Programs during the COVID-19 Pandemic: What is restricted and who decides?. (15th December 2022) - Mena Lora, Alfredo J; Herald, Fischer; Lindsey, Brenna; Burgos, Rodrigo M; Borgetti, Scott; Chaisson, Lelia H; Bleasdale, Susan C
Abstract: Background: During the COVID-19 pandemic, evolving literature and emerging therapies have led to significant controversies on what constitutes optimal therapy for hospitalized patients with COVID-19. In addition, multiple guidelines emerged exhibiting variable recommendations in key areas of therapeutic management. Thus, interpreting emerging data and deploying novel therapeutics during the pandemic has been challenging. Antimicrobial stewardship programs (ASP) have been proven to help promote evidence-based practices and are now common the United States (US). We seek to further understand the role of ASP during the COVID-19 pandemic. Methods: A survey was developed and disseminated through Infectious Diseases Society of America (IDSA) IDea network, IDSA Antimicrobial Stewardship Centers for Excellence and the Society for Healthcare Epidemiology messaging boards. Data collected included city, hospital size, facility type, and existence of active ASP. COVID-19 therapeutic restrictions and type of provider who decides on treatment allocation was surveyed. Results: A total of 92 surveys were completed, representing wide geographic reach within the United States (Figure 1). Hospital size by beds were 14% less than 200 (13), 18.5% 201-300 beds (17), 15.2% 301-400 beds (14), and 52.2% over 400 beds (48). Community hospitals accounted for 31.5% (29), county/public hospital 3.3% (3, 3.3%), University-affiliated Community-Based Teaching Hospitals 10.9% (10), University-based Teaching Hospital 45.7% (42), and 8.7% selected other. ASP were present in 97.2% of hospitals. COVID-19 therapeutic restrictions were common (Figure 2). Infectious diseases (ID) approval was required in 87.9% of facilities (Figure 3). Figure 1 Geographic distribution of hospitals represented in the survey Figure 2. Restricted COVID-19 therapies by medication type (%) Figure 3 Specialties or providers that are able to order or approve restricted COVID-19 therapies (%) Conclusion: COVID-19 therapeutics were commonly restricted during the COVID-19 pandemic. Approval by ID clinicians was required almost universally (87.9%). The role of other specialties was significantly lower, representing less than 45% of hospitals. ID clinicians have played a vital role in guiding therapy and supporting ASP during the COVID-19 pandemic. This survey highlights the value of ID clinicians to healthcare systems in allocating resources and promoting evidence-based practices through ASP. Disclosures: All Authors : No reported disclosures.